Sejarah Agama dalam Kajian Al-Quran - Rahayu, Endang Sri (Adh Dhiya | Journal of The Quran and Tafseer Studies, 2023)
The study of religion has been carried out with various approaches. Starting from cultural approaches, anthropology, phenomenology, sociology and psychology. To complete the discussion about religion and including its history, the author will examine religious studies through the approach of the sacred Qur'an, by understanding the meaning of religion, as well as comparing religion with Magi, explaining religion as human nature, religion as God's guidance, the relationship between religion and Sharia. 'Ah. Explaining the entities of the Prophets, such as Noah, Abraham, Moses, Jesus and Muhammad by referring to the verses of the Koran, will clarify the meaning of the Samawi religion.